2008
DOI: 10.21273/horttech.18.1.59
|View full text |Cite
|
Sign up to set email alerts
|

Postestablishment Landscape Performance of Florida Native and Exotic Shrubs Under Irrigated and Nonirrigated Conditions

Abstract: Although new and innovative measures to reduce landscape water consumption are being sought, traditional methods of water restrictions and plant selection prevail. Species native to North America are often promoted as drought tolerant with little information to support or refute such claims. Furthermore, species performance is unknown in maintained environments such as commercial and residential landscapes. Thus, 10 native and 10 exotic species, commonly used in landscapes, were evaluated independently… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 13 publications
1
13
0
Order By: Relevance
“…Our data also suggest that there were no differences in canopy growth or aesthetic quality of native versus non-native shrubs at any of the planting locations (Tables 2 and 3). Our results are similar to those of Scheiber et al (2008), who found that neither native species nor non-native species were, as a group, more responsive to irrigation. Scheiber et al (2008) reported that growth of two of 10 Florida natives and two of 10 non-natives increased when irrigated (daily for 17 d, then every 2 d for 7 weeks, then every 7 d).…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations
“…Our data also suggest that there were no differences in canopy growth or aesthetic quality of native versus non-native shrubs at any of the planting locations (Tables 2 and 3). Our results are similar to those of Scheiber et al (2008), who found that neither native species nor non-native species were, as a group, more responsive to irrigation. Scheiber et al (2008) reported that growth of two of 10 Florida natives and two of 10 non-natives increased when irrigated (daily for 17 d, then every 2 d for 7 weeks, then every 7 d).…”
Section: Resultssupporting
confidence: 90%
“…Scheiber et al (2008) reported that growth of two of 10 Florida natives and two of 10 non-natives increased when irrigated (daily for 17 d, then every 2 d for 7 weeks, then every 7 d). Enhanced growth of irrigated shrubs seemed to be associated with species habitat preference because all species that increased in growth as a response to irrigation were endemic to wet habitats (e.g., swamps and streams) (Scheiber et al, 2008).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It was assumed that each landscape consisted of 79% well‐watered turfgrass and 21% ornamental plant beds (Haley & Dukes ). The irrigation requirement of the ornamental plant beds, which typically don't need supplemental irrigation after six to 12 months of planting, was assumed to be zero (Shober et al , Scheiber et al ).…”
Section: Irrigation Metricsmentioning
confidence: 99%